2018
DOI: 10.4315/0362-028x.jfp-17-412
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Aflatoxin B1 Binding by the Cell Wall and (1→3)-β-d-Glucan of Baker's Yeast

Abstract: The aim of this study was to evaluate the ability of heat-killed baker's yeast (HKBY), the cell wall of baker's yeast (CWBY), and cell wall (1→3)-β-d-glucan of baker's yeast (BGBY) to bind aflatoxin B (AFB) in phosphate-buffered saline (PBS) spiked with 0.5 μg/mL AFB. Baker's yeast ( Saccharomyces cerevisiae) was heat killed by autoclaving at 121°C for 10 min. The cell wall was physically extracted, and (1→3)-β-d-glucan was extracted by a modified method. The concentration of AFB was determined by high-perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…According to Joannis-Cassan et al (2011), βglucan derived from Saccharomyces cerevisiae might lower AFB1 by up to 29%. This was also demonstrated by Yiannikouris et al(2006), who reported that the adsorption range of AFB1 by β-glucan was 22Á8-59Á7%, whereasAazami et al (2018) reported that it was 6Á30-46Á34%. Meanwhile, yeast isolates identified as Kluyveromyces marxianus and Pichia kudriavzevii demonstrated AFB1 detoxification in up to 85%(Intanoo et al 2018).…”
supporting
confidence: 64%
See 1 more Smart Citation
“…According to Joannis-Cassan et al (2011), βglucan derived from Saccharomyces cerevisiae might lower AFB1 by up to 29%. This was also demonstrated by Yiannikouris et al(2006), who reported that the adsorption range of AFB1 by β-glucan was 22Á8-59Á7%, whereasAazami et al (2018) reported that it was 6Á30-46Á34%. Meanwhile, yeast isolates identified as Kluyveromyces marxianus and Pichia kudriavzevii demonstrated AFB1 detoxification in up to 85%(Intanoo et al 2018).…”
supporting
confidence: 64%
“…(2006), who reported that the adsorption range of AFB1 by β‐glucan was 22·8–59·7%, whereas Aazami et al . (2018) reported that it was 6·30–46·34%. Meanwhile, yeast isolates identified as Kluyveromyces marxianus and Pichia kudriavzevii demonstrated AFB1 detoxification in up to 85% (Intanoo et al .…”
Section: Determination Of Anti‐lipid Peroxidationmentioning
confidence: 99%
“…34 Also, it has been displayed that (1→3) β-D-glucan is the most efficient binder on the surface of S. cerevisiae cell wall. 35 The cell wall of this yeast has been mostly made up of polysaccharides (80-90%). An inside layer composed of β-D glucans is responsible for the mechanical resistance of cell wall.…”
Section: Resultsmentioning
confidence: 99%
“…The adsorption capability mainly depended on yeast composition and mycotoxin. Earlier studies investigated that yeast cells had the ability to attach numerous molecules involving mycotoxins via the polysaccharides (glucans), mannoproteins, and lipids found on their cell wall surface [ 32 ]. They can bind to the hydroxyl, ketone, and lactone groups of AFs by hydrogen bonds and van der Waals forces [ 33 ].…”
Section: Discussionmentioning
confidence: 99%